Divergência genética em aveia-branca com base na expressão fenotípica, marcadores moleculares e reação à brusone - Santos, Jossana (2016)
The increasing economic importance of white oat (Avena sativa L.) challenges breeders in launching increasingly competitive materials. Morphological characterization is essential in the process of protecting new cultivars, but it has some limitations, such as environmental influence on descriptors. Studies of genetic diversity, by using molecular markers, such as microsatellites, and also phytopathological reviews, have become complementary activities to the morphological characterization. This work aimed to evaluate five cultivars of white oat (IPR Afrodite, URS Corona, FAEM Carlasul, UPFA Ouro and URS Taura), as the expression of morphophenological descriptors, molecular markers and reaction to blast. 1) The expression of the front descriptors of environmental variability was evaluated in two periods of cultivation in (Fall-Winter) and outside the recommended period (Winter-Spring) to the culture. The experiment was set up in the field, in a randomized block design with three replications, in which the cultivars were evaluated for stability of 42 descriptors. The delay in the white oat growing season, from Fall-Winter to Winter-Spring, reduced the cycle, modified the morphological expression of most descriptors and changed phenotypic divergences among cultivars. 2) The genetic divergence among cultivars was verified by 47 microsatellite markers. DNA was extracted from young plants, with subsequent PCR amplification, agarose gel electrophoresis and through ethidium bromide visualization. The number of alleles per locus and the polymorphic information content (PIC) was calculated. The cultivars were grouped by Dice index and the Tocher method, with the formation of three and two groups, respectively. Markers amplified a total of 29 alleles with an average of 1.8 alleles per locus and PIC 0.45. Microsatellite markers were useful in determining the genetic divergence between white oat cultivars. 3) For the analysis of the reaction to blast on leaves, it were used four isolates of Pyricularia oryzae. In nine assessments under controlled conditions, it were quantified: the number and expansion of the lesions, severity and area under the disease progress curve. The leaves were histochemically evaluated in pre-inoculation and 48 hours post-inoculation of the fungus to verify the possible effects of the disease on the chemical groups, lipids, lignin, phenols, flavonoids and tannins. Data were submitted to analysis of variance, regression and multivariate analysis. The leaves showed an increase on flavonoids concentration in the fungus post-inoculation. The cultivars presented variability in reaction to the blast. In lower order to higher susceptibility it was observed: URS Taura < UPFA Ouro < IPR Afrodite < FAEM Carlasul < URS Corona.